HGG-48. A comparative proteomic analysis of the cell membrane of histone 3 mutated paediatric high-grade gliomas in order to identify potential immunotherapeutic targets. (3rd June 2022) - Suresh, Sneha; Khan, Alina; Snary, Anya; Pickering, James; Rahman, Ruman; Grundy, Richard; Layfield, Robert; Haque, Farhana
Abstract: Improvements in the treatments for childhood and adolescent brain tumours, High-Grade Glioma (pHGG) and Diffuse Intrinsic Pontine Glioblastoma (DIPG), have not advanced much and they continue to carry a very poor prognosis. These brain tumours are now defined by mutations affecting histone 3 proteins, indeed 80% of DIPGs harbour histone H3.1 and H3.3 K27M somatic mutations whilst 30% of pHGGs exhibit H3.3 G34R or G34V mutations. We hypothesized that the histone 3 mutant tumours will have distinct mutation specific surfactome or cell surface proteins. We therefore analysed the cell surface proteomics of H3.3 G34V and G34R mutated high-grade glioma in comparison to the H3 wild-type Glioma, to explore whether these proteins have the potential to be used as immunotherapeutic targets. We have at first isolated the cell membrane fractions from a range of patient cells carrying histone 3 mutations (G34R, G34V) relative to wild type histone 3. A comparative quantitative liquid chromatographic mass-spectrometry analyses of these cell surface membrane fractions were performed to identify specific targetable factors. The results of these were analysed with the focus in identifying proteins that can be targeted for tumour specific immune modulation or immunotherapeutic intervention. Results of these analyses will be presented.